Development of Teaching Materials Based on Local Wisdom Values of Balaputra Dewa Museum for Geography Learning at SMA 11 Palembang - Romansyah, Abdul; Asiyah, Siti; Monanisa, Monanisa (Raudhah Publisher, 2024)
The purpose of providing modern and professional health services is By paying attention to local cultural values and adopting these cultural values as an effort to adapt to the culture of the community in achieving the goals of modern health services. There are two research methods used by researchers in the field of social sciences, namely the quantitative method and the qualitative method. This process provides an overview of the researcher's efforts in processing the data in depth and elaborating the research database until the researcher succeeds in building a complete data set. In this process, the researcher involved respondents interactively. The results of the study show that health services are carried out according to MTBS standards. The access to referrals from the health center to the hospital is quite far, so assistance for MTBS patients with severe conditions is difficult to handle, and this is a large contributor to the infant mortality rate. The variables of officer characteristics and other factors outside the treatment of the children studied, the service process is very different in each development area.